Guyana. Significant achievements 2014 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamerica de Cooperación para la Agricultura (IICA), 2016)
The main activities carried out by the Institute in Guyana during 2014 are identified, with respect to the needs and interests of the country, strengthening issues such as Greenhouses, exports, imports, technology, biogas, waste management, revolving fund, inclusion of women, resilience against climate change, production of vegetables, fruits and in the control of pests such as the fruit fly.